ANALISIS KINERJA PETUGAS ADMINISTRASI DALAM PELAYANAN VAKSIN COVID-19 DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Tonis, Marian; Padilla, Raihan safa; Purnamasari, Devi (Journal of Hospital Administration and Management (JHAM), 2023)
Performance is a result of work achieved by a person in carrying out the tasks assigned to him Arifin Achmad Hospital. The purpose of this study was to find out how the performance of the officers in the covid-19 vaccine service division at the Arifin Achmad Hospital By using performance indicators, namely the quality of work and working time. his research was conducted from September 19 to October 19, 2022 this research uses a qualitative research type. Data analysis in this study uses a descriptive method, namely describing the data collected in the form of words, pictures, and not numbers, the purpose of data analysis is data. to make it easier to understand, and then make a conclusion. The results of the study show that the performance of administrative officers in the Covid-19 vaccine service has obstacles, this can be seen from the officers who need additional, the existence of facilities to support the performance of officers for the better, and also for the implementation of related training and the unavailability of SOP (Standard Operating Procedure). It is recommended that the Covid-19 vaccine service at the Arifin Achmad Hospital in Riau Province regarding the addition of officers, infrastructure facilities that help the performance of officers to be better.